Surface settlements induced by shallow tunnels- The case of Athens Metro - Papadopoulou, K.V. (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World, 2023)
The effects of ground displacements on surface structures due to shallow tunnels in urban environment are of great importance. Simplified methods predicting the transverse settlement trough in greenfield conditions are widely used. However, the investigation of the ground movements development is facilitated by the results from numerical analyses and the evaluation of in situ measurements, as well. Firstly, in the present paper, the effect of the most important factors on surface settlements is investigated and commented, applying finite element analyses for the case of TBM tunnels. Extended parametric 3D F.E. analyses are carried out using the Hardening Soil Model for two representative soil types, simulating the cases of a weathered weak rock and a very stiff clay. The geological and geotechnical conditions of the formations encountered during the construction of the Athens (Greece) Metro, driven through weathered weak rock, the so-called Athenian schist are briefly presented and evaluated. The results from back analyses using 3D F.E.M. for representative cases are compared with the corresponding measurements of surface settlements developed during the construction. These measurements are also related with the best fitting curve using the well-known equation after Gauss. Moreover, the distance of the maximum rotation of the surface (inflection point) from the center line, predicted from the 3D F.E. analyses, is compared with this resulted from the measurements. The effects of ground displacements on surface structures due to shallow tunnels in urban environment are of great importance. This chapter investigates the effect of the most important factors on surface settlements, applying finite element analyses for the case of tunnel boring machine (TBM) tunnels. It presents indicative back analyses regarding the settlement trough due to the construction of Athens Metro, in conjunction with the relevant measurements. The Athens Metro has been driven by different methods for the various lines or parts of lines, as TBM, earth pressure balance -TBM or Conventional Excavation, depending on both geological conditions and the restrictions of the surface settlements. The effects of some important factors on the surface settlements and settlement profile due to a shallow tunnel driven in greenfield area are examined by 3D finite element analyses. Among the empirical solutions, the most widely used is the approximation of the settlements trough in greenfield conditions by the Gaussian curve.